Perfluorocarbon inhibits lipopolysaccharide-induced macrophage inflammatory protein-2 expression and activation of ATF-2 and c-Jun in A549 pulmonary epithelial cells - Hu, Y; Li, C S; Li, Y Q; Liang, Y; Cao, L; Chen, L A (Cellular and Molecular Biology, 2016)
The signaling pathway that mediates the anti-inflammatory effects of perfluorocarbon (PFC) in alveolar epithelial cells treated with lipopolysaccharide (LPS) remains unclear. To evaluate the role of macrophage-inflammatory protein-2 (MIP-2), four A549 treatment groups were utilized: (1) untreated control, (2) 10 Î¼g/mL of LPS, (3) 10 Î¼g/mL of LPS+30% PFC and (4) 30% PFC. MIP-2 mRNA expression was determined by qPCR and ELISA. Mitogen-activated protein kinase (MAPK) activation was determined by Western blot analysis, and MIP-2 expression was determined by qPCR following treatment with MAPK inhibitors. PFC suppressed LPS-induced MIP-2 mRNA levels (Pâ‰¤0.035) and MIP-2 secretion (Pâ‰¤0.046). LPS induced ATF-2 and c-Jun phosphorylation, which was suppressed by PFC. Finally, inhibitors of ERK, JNK, and p38 suppressed LPS-induced MIP-2 mRNA expression. Thus, PFC inhibits LPS-induced MIP-2 expression and ATF-2 and c-Jun phosphorylation. To fully explore the therapeutic potential of PFC for acute lung injury (ALI), in vivo analyses are required to confirm these effects.